2008
DOI: 10.1093/rpd/ncn031
|View full text |Cite
|
Sign up to set email alerts
|

Results of a European survey on patient doses in paediatric radiology

Abstract: Paediatric patients represent a very specific group within the radiology department. Compared to adult patients, they are more sensitive to radiation. As they are sometimes submitted to several radiology procedures, dose and image quality should be well balanced. Nowadays, only a few centres specialize in paediatric imaging, and knowledge of paediatric patient doses is, therefore, very scattered. The effect of the introduction of digital technology on paediatric patient doses remains largely undocumented. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…The improved technology and optimisation of imaging protocols have resulted in much lower doses [2231], while the risk for heritable disease has been found to be lower than previously assumed [32]. The question then arises whether today’s reduction in radiation risk by applying gonad shielding is still worthwhile in view of its negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The improved technology and optimisation of imaging protocols have resulted in much lower doses [2231], while the risk for heritable disease has been found to be lower than previously assumed [32]. The question then arises whether today’s reduction in radiation risk by applying gonad shielding is still worthwhile in view of its negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…To be able to keep doses as low as reasonably achievable (ALARA), fundamental knowledge of factors concerning patient doses is needed. Pediatric examinations comprise approximately 10% of all radiological examinations, which may result in situations in which pediatric examinations are not well optimized due to a lack of knowledge in choosing the proper acquisition parameters (3). particular clinical problem (4).…”
mentioning
confidence: 99%
“…Th e Radiographer 2011 21 exposed when young. 20 At ages up to 10 years, children are up to three times more sensitive to radiation than adults.…”
Section: Original Article Volume 58 (3) 2011mentioning
confidence: 99%
“…20 At ages up to 10 years, children are up to three times more sensitive to radiation than adults. 21, 22 Brenner, et al found that a single 15 mSv CT examination, equivalent to 500 standard chest x-rays, has an impact on a child of twice that on an adult. 23 Children's lifetime cancer risk is increased due to both higher radiation sensitivity and longer expected life span.…”
Section: Original Article Volume 58 (3) 2011mentioning
confidence: 99%
See 1 more Smart Citation